Don't tell me I'm normal: inpatient psychotherapy of a severely abused patient at the Cassel Hospital. Issue 3 (2nd July 2016) - Glyn, John
Abstract: This paper is a case study of a patient with severe personality disorder undergoing treatment at the Cassel Hospital. It looks at a phase of her individual psychoanalytic psychotherapy and how that sits within an institutional model of treatment that can be understood as applied psychoanalysis, in which Tom Main's concept of a 'culture of enquiry' aims to observe and bring together splitting and projective processes operating at all levels of the organisation. The patient, who had been sexually abused and then suffered a prolonged suicidal breakdown, exerted intense pressure on the institution through her experience of herself as both a victim of abuse and a participant in it. A working through is described, in which different parts of the patient that had been projected into different parts of the institution are brought together, and her primitive demand for a two-person world gives way to an acceptance of triangulation. Themes from her individual sessions are enacted in the milieu-based treatment, and conversely struggles in the patient community appear in her sessions. It is from drawing these parts of the patient together as a whole institution that the treatment derives its power and effectiveness.